Keberhasilan Mediasi Perkara Perdata di Pengadilan Negeri Pamekasan Mengacu pada Perma Nomor 1 Tahun 2016 - Talitha Rahmaningtyas (Bulletin of Community Engagement, 2024)
Mediation in the District Court is used as a settlement using a third party, namely a mediator. Mediation is used to reduce the burden of litigation and provide dispute resolution with a middle way in the form of peace by taking a middle way through a mediator. Mediation is also called a middle way in resolving cases. Mediation is used as a peaceful and effective solution because it can enable the parties to reach a fair solution without taking sides. In this research the author discusses how successful mediation is used in resolving civil cases at the Pamekasan District Court. This research contains the role of judges as mediators in carrying out the mediation process in court. This research contains about the success of mediation carried out by mediator judges at the Pamekasan District Court referring to Perma No.1 of 2016 concerning Mediation Procedures in Court. From the information that has been explained, the aim of this research is to find out how the Mediation Procedure is implemented in the Court and find out the level of success of mediation in the Class 1B Pamekasan District Court after the enactment of Perma No.1 of 2016.